Instilling Aswaja Values in Shaping Moderate Religious Attitudes among Students at Salafiyah Islamic Boarding Schools - Rohmadi, Rohmadi; Halimatussakdiah, Halimatussakdiah; Azwar, Alfi Julizun; Almaher, Ali Akbar; Oktaviana, Diah; Kahfi, As Habul; Syarif Zain, Zaki Faddad (PAI RAFAH, 2026)
This study analyzes efforts to instill Ahlussunnah wal Jama'ah (Aswaja) values in shaping religious moderation attitudes among santri at Salafiyah Rubath Al Muhibbien Islamic Boarding School, Palembang. Aswaja values emphasizing balance, tolerance, and harmony serve as a vital foundation in facing modernity and religious polarization challenges. Using a qualitative-descriptive approach, data were collected through in-depth interviews, participatory observation, and document analysis involving pesantren leaders, ustadz/ustadzah, and santri. Thematic analysis was applied to identify key patterns, with validity ensured through source and method triangulation. Findings reveal that Aswaja values are instilled systematically through classical Islamic text studies (kitab kuning), routine religious activities, and tolerance-building in daily interactions. These values effectively cultivate moderate attitudes, reflected in santri's ability to appreciate differing views, maintain social harmony, and reject extremism. Challenges include the influence of digital technology and external pressures. These findings emphasize the importance of synergy between pesantren education and contextual approaches to build an inclusive and tolerant generation.